The Political Elite of Ukraine: Historical and Sociological Analysis - Pylypenko, V.; Privalov, Yu. (Социология: теория, методы, маркетинг, 2016)
The paper discusses the main problems of the national political elite and specific features of their functioning. Special attention is paid to the process of coming into being of Ukraine s political elite, which is described in the context of formation of the Ukrainian statehood.